Implementasi Kurikulum Pendidikan Agama Islam Pada Siswa Tunagrahita - Firmansyah Muhammad Tauhid; Triana Rosalina Noor (Prodi Pendidikan Keagamaan Islam, 2026)
This study aims to describe the implementation of the Islamic Religious Education (PAI) curriculum for students with intellectual disabilities at SMALB Al-Chusnaini, focusing on the objectives, materials, methods, and evaluation of learning. The study employed a qualitative approach using a case study design. The research subjects consisted of five participants selected through purposive sampling. Data were collected through observation, interviews, and documentation studies from October to December 2025, and were analyzed using the Miles and Huberman model with source triangulation. The results showed that the implementation of the PAI curriculum refers to the Merdeka Curriculum with an adaptive and humanistic approach. The learning objectives emphasize the cultivation of monotheistic values, the habituation of worship practices, and character development. PAI materials are simplified according to the abilities of students with intellectual disabilities and delivered contextually. The learning methods are integrative, involving lectures, practical activities, and habituation, while evaluation is conducted through observations of students’ religious behavior. The challenges in implementation include teachers’ workload, differences in students’ characteristics, suboptimal parental involvement, and limitations in facilities and infrastructure.